Pelatihan Pengembangan Program Kewirausahaan Berbasis Teknologi Diversifikasi Ikan Patin Sebagai Produk Hilirisasi Menuju Komersialisasi Pada Kelompok Kewirausahan Fisheries Product Club - Suparmi Suparmi; Sumarto Sumarto; Windarti Windarti; Mery Sukmiwati; Lapeti Sari; Rizky Febriansyah Siregar; Nofri Sandria; Ranika Paramita (CANANG: Jurnal Pengabdian Masyarakat, 2025)
The Science and Technology-Based Entrepreneurship Development Program (PPKBI) plays a crucial role as a form of downstream research translation towards commercialization. This community engagement initiative is expected to enhance collaboration with partners, in this case, a student entrepreneurship group known as the Fisheries Product Club (FPC). The downstream products have already been granted simple patents, namely Ubikan Fish Nugget (Patent No. IDS000004954) and Anekarasa Catfish Macaroni (Patent No. IDS000005784). The objective of this program is to provide opportunities to accelerate the development of a culture of utilizing university research outputs for the benefit of the community, as well as to foster cooperation with partners, including industry and marketing sectors. The implementation method employed the Participatory Action Learning System (PALS), which is fundamentally based on engaging students in an active and naturally participatory learning process within the entrepreneurship program through training. This approach forms an interactive, participatory learning system, both at the individual and group levels. A total of 20 participants, all members of the FPC, took part in the program. The training yielded positive responses and motivated participants to embark on entrepreneurial activities. The products, Anekarasa catfish macaroni and Ubikan fish nuggets, hold strong potential to be developed as viable business opportunities for emerging entrepreneurs